Does Imported Input Affect Export Quality? Case of Indonesia in The Period of 2010-2015 - Kiki Verico; Tiura Herlinda (Journal of Developing Economies, 2023)
This study aims to find empirical evidence of whether importing input as an external source of knowledge and technology transfer for developing countries affects export quality. Empirical data shows that over 75 percent of Indonesia's total import values are intermediate products used in the manufacturing process. This study combines custom data with a dataset of Indonesia's Firm-Level data of the Large and Medium Manufacturing Industry from 2010 to 2015. It applies the fixed-effect regression method and finds that imported input has a less significant effect on the export quality. Given its numerous populations, this study indicates that increasing imported input aims to meet Indonesian domestic demand instead of export quality.